The Influence of Corporate Governance on Financial Performance With Risk Management as Mediating Variable - Nurna Aziza; Niken Kenanga Aviola (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
This study examined the relationship between corporate governance mechanisms, risk management, and financial performance of banks in Indonesia. The sample comprised 160 banking entities listed on the Indonesia Stock Exchange from 2014 to 2018, chosen through purposive sampling. The data were analyzed using path analysis with AMOS version 22. The findings revealed that corporate governance significantly influenced risk management in the banking industry. Effective corporate governance mechanisms positively impacted risk management practices, indicating that well-governed banks were more likely to implement robust risk management strategies. Moreover, the study found that risk management played a crucial role as an intervening variable between corporate governance and financial performance. This suggests that the influence of corporate governance on financial performance was partially mediated through its impact on risk management practices. Additionally, the results demonstrated a significant positive effect of corporate governance on the financial performance of banks in Indonesia. Well-governed banks tended to exhibit better financial performance, likely due to their ability to manage risks more effectively and make sound strategic decisions. The study highlights the importance of strong corporate governance practices in enhancing risk management and subsequently improving the financial performance of banks. These findings have implications for regulators, bank management, and investors, emphasizing the value of promoting effective corporate governance in the banking sector to achieve sustainable financial growth and stability. Keywords: banking, corporate governance, financial performance, mediating variable, risk management